The extension of organisational readiness model towards technology migration : A case of IPV6 migration - Main, Aspalilla (2017)
Internet Protocol, often referred to as IP, is the Internet addressing protocol that allows devices to connect to each other. At present, the existing Internet Protocol Version 4 (IPv4) is being gradually replaced by a new version of the protocol, Internet Protocol Version 6 (IPv6), to provide a larger scale of addresses and to facilitate various improvements to the protocol. Migration from IPv4 to IPv6 is seen as a lengthy and difficult process for any organisation as it comprises many aspects such as talent management especially the IT personnel and technology competence in terms of the current infrastructure capability to facilitate IPv6 environment and the process which include testing and implementation. The highlighted issue in this study is that in most places, the IPv6 deployment process is quite slow, despite the crucial changes to the new protocol. This concern is contributed by the fact that many organisations are still not prepared for the migration to the IPv6 even though they are aware of the serious needs to apply it in their network. Factors that influence the readiness of an organisations towards IPv6 have been studied from different aspects and perspectives by previous studies, therefore, the objectives of this study were to analyze the physical and human factors that can define the readiness of an organisation to migrate to the IPv6; to develop the IPv6 organisation readiness model based on categorized factors and to validate the IPv6 organisation readiness model. A mix-method research strategy was applied in this research which consisted of two phases; determine the factors (qualitative) for the early phase and model development and reliability and validity (quantitative) for the second phase of the study. For the qualitative approach, document analysis and structured interviews were chosen as the research instrument for the data collection involving five experts to explore the factors. Manual approach to transcribe the findings or coding was used for the data analysis of the interview. For the next phase, data were collected from 107 IT personnel who were managing the computer networks in polytechnics and community colleges throughout Malaysia, and a 5-point Likert Scale questionnaire was employed as the data instrument. Rasch measurement model was applied as a direction for data analysis and the data were analysed using the statistical analysis software, Winstep version 3.69.1.11, to determine the most important factor towards IPv6 migration and to validate the model as well. The results revealed that equipment, cost, deployment, motivation, skill and knowledge were the factors required for migration to the IPv6 and the most important factor in physical category was deployment (mean measure=-0.20, mean score=4.4) and the most important factor in human category was skill (mean measure=-0.62, mean score=4.52). For the model validity, the unidimensionality test revealed that each factor was proven based on the independent items and model fit. In conclusion, the results significantly proved that the factors had high potentials to measure the readiness of an organisation for IPv6 migration.